Case report: An occult hepatitis B virus infection reactivation in an HIV/HCV coinfected patient during an immune reconstitution inflammatory syndrome - Zaltron, Serena; Cambianica, Anna; Di Gregorio, Marco; Colangelo, Cosimo; Storti, Samuele; Tiecco, Giorgio; Castelli, Francesco; Quiros-Roldan, Eugenia (Frontiers in Cellular and Infection Microbiology, 2023)
The natural history of occult hepatitis B virus infection (OBI) and the mechanism involved in HBV reactivation are only partially understood. As regards people living with HIV (PLWH), HBV reactivation is estimated to occur with an incidence ratio of 0.019 cases per 100 person-year. Here we report the case of OBI reactivation in a HIV/HCV co-infected patient followed for 25 years at our Infectious Diseases Unit, but, unfortunately, lost to follow-up about 19 months after Direct-acting antivirals (DAAs) treatment. At re-engagement, blood tests showed high replication of plasmatic HIV-RNA along with severe immunosuppression and normal levels of liver enzymes. However, 3 months after ART reintroduction, an immune reconstitution inflammatory syndrome (IRIS) was diagnosed with high detectable HBV-DNA load and transaminase elevation. Our case report shows how the balance between the virus and the host immune system is quite a dynamic process that might significantly impact the course of the disease. The aim of this case report is to bring to the attention of physicians that, although OBI reactivation is a rather rare occurrence, even amongst PLWH, its potential consequences compel to a high alertness on the matter. Therefore, especially in patients with an impaired immune system and on a tenofovir or lamivudine-sparing regimen, HBV serological and virological markers should always be strictly monitored, even in the absence of a hepatitis flare.